The Representation of Citizenship Values in Arabic Textbooks: Marrying Delanty and Hopkins Concepts - St Kuraedah (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
Although research on citizenship values in language textbooks has been widely documented, little is known about citizenship values in Arabic textbooks at Indonesian Islamic Junior High Schools. To extend this scholarship, the present study examines the values of citizenship in those textbooks and how they are presented. Data collection was carried out using document analysis techniques in three textbooks. Data analysis was carried out using a combination of Delanty and Hopkins concepts of citizenship values. The findings revealed that eight aspects of civic values are found in textbooks presented in reading materials, conversations and training materials. They are honesty (1.23%), rights (6.79%), courage (8.33%), compassion (15.43%), participation (15.74%), respect (16.35%), identity (17.90%), and responsibility (18.20%). This finding implies that Arabic textbooks in Indonesian Islamic Junior High Schools should be conducted by incorporating citizenship values equally, such as honesty, rights, and courage. Since students are supposed to become the nation's successors who have allegiance to the state, nation, and religion, these values should be instilled in them from an early age.